2012
DOI: 10.1007/s11250-012-0320-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subclinical mastitis and isolated udder pathogens in dairy cows in Southern Vietnam

Abstract: Dairy production is not traditional in Vietnam. The farmers have little practical knowledge and udder health control is generally lacking. In order to give the farmers appropriate advice, knowledge about the distribution of udder pathogens is crucial. The aim of the study was to investigate the prevalence of sub-clinical mastitis and to identify udder pathogens isolated from smallholder dairy herds in Southern Vietnam. Twenty farms with a herd somatic cell count (SCC) ranging from low (≤ 400 × 10(3)cells/mL) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
3
23
2
Order By: Relevance
“…This confirms that the prevalence of coliform bacteria in this study would be low, as few samples were of clinical mastitis. Although environmental Streptococcus agalactiae (6.5%) were ranked third in the current study, the microorganism have been reported as the most prominent bacteria in cow mastitis in some countries [26,45]. The prevalence rate of S. agalactiae reported in the current study agrees with previous findings observed elsewhere [35,59].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This confirms that the prevalence of coliform bacteria in this study would be low, as few samples were of clinical mastitis. Although environmental Streptococcus agalactiae (6.5%) were ranked third in the current study, the microorganism have been reported as the most prominent bacteria in cow mastitis in some countries [26,45]. The prevalence rate of S. agalactiae reported in the current study agrees with previous findings observed elsewhere [35,59].…”
Section: Discussionsupporting
confidence: 90%
“…Vietnam [45]. It has been pointed out by previous authors that subclinical mastitis is a complex disease and discrepancies in the reported incidences in different studies could be attributed to differences in animal breeds, management systems, parity, teat morphology, and milking hygiene [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the prevalence rate of clinical and subclinical mastitis of different mastitis pathogens in a cow population from small-scale dairy herds are scarce. Although it is difficult to compare results obtained in this work with those obtained in other countries, CNS, S. aureus , and streptococci have been reported to be the most prevalent pathogens [52, 53]. Alternatively, bacteriocins of B. thuringiensis inhibited the growth of different bacteria tested here and they could have a viable potential for use in integrated management programs to control or prevent mastitis in animals.…”
Section: Discussionmentioning
confidence: 60%
“…Blood of each mouse was collected and the serum samples obtained by centrifugation were kept frozen at -20 o C. The entire spleen and thymus of mice were promptly removed after killed and weighed. The spleen and thymus indexes were calculated according to the formulas: (spleen or thymus weight / body weight) × 100% [23].…”
Section: Samples Collection and Detection Of Thymus And Spleen Indexesmentioning
confidence: 99%
“…When pathogenic microorganisms invade the mammary gland via the teat orifice and cause an inflammation of the secretory tissue, manifesting itself in either clinical or sub-clinical mastitis [29]. Over 200 agents have been recorded to cause bovine mastitis [2], but the vast majority of cases were caused by Staphylococcus aureus, Streptococcus dysgalactiae, Streptococcus agalactiae, Escherichia coli and Streptococcus uberis [15,17,23].…”
Section: Introductionmentioning
confidence: 99%